2014
DOI: 10.1136/bjophthalmol-2014-305449
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of conventional versus crossed monovision in pseudophakia

Abstract: KCT0001065.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…There are reports regarding improvement in stereopsis following management of congenital cataract, management of monocular aphakia, or secondary lens implant. 4,[31][32][33][34][35][36] Similar results are found in the current study.…”
Section: Discussionsupporting
confidence: 91%
“…There are reports regarding improvement in stereopsis following management of congenital cataract, management of monocular aphakia, or secondary lens implant. 4,[31][32][33][34][35][36] Similar results are found in the current study.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, some studies revealed that multifocal group has better near visual function when compared to monovision group 23. The current study has similar results to that reported by crossed monovision technique 26…”
Section: Discussionsupporting
confidence: 89%
“…This does not have seem to make any difference in the outcomes, as it was shown in the earlier published studies that patient satisfaction as well as the visual results of crossed monovision were no different from conventional monovision. [26][27][28]…”
Section: Discussionmentioning
confidence: 99%